Importance of the Secondary Genepool in Barley Genetics and Breeding II. Disease Resistance, Agronomic Performance and Quality - R. Pickering; R.E. Niks; P.A. Johnston; R.C. Butler (Czech Journal of Genetics and Plant Breeding, 2004)
In this second paper on the use of secondary genepools in barley improvement, we describe the characterisation of leaf rust resistant recombinant lines (RLs) derived from Hordeum vulgare × H. bulbosum crosses. Twelve RLs were inoculated with leaf rust and the early stages of disease development were observed. Several RLs showed complete resistance to the pathogen, but others had a high level of partial resistance, which may be durable. Some of these RLs and others were tested in yield trials to determine the effects of introgressed chromatin from H. bulbosum on yield and quality. We conclude that there are no major adverse effects that cannot be overcome through normal breeding techniques.